Avaliação clínica de diferentes protocolos de laser de baixa potência em mucosite bucal induzida por 5-fluouracil em hamsters - Kaefer, Thieni (2012)
Aims: The purpose of this study was to investigate the effects of different of low level laser (LLL) protocols on induced-oral mucositis by 5-fluoracil (5-FU) in hamsters. Introduction: The oral mucositis is a ordinary side effect from antineoplasic therapy. Development of effective interventions to its prevention and treatment are priory on caring of the oncology patients. Metodologia: In the present study 96 hamsters were used and randomly allocated into 4 groups: Control (without treatment), Preventive (laser from day -5 to day +5), Therapeutic (laser from day +5 to day +15) and Combined (laser from day -5 to day +15). Mucositis was induced in hamsters by intraperitoneal injection of 5- fluorouracil (5-FU) at days 0 and 2 and superficial scratching in cheek pouch mucosa. The irradiation was carried out using diode LLL, 660 nm, 40mW of power, 6,0J/cm2 during 6seconds/point. At days 0, 5, 10 and 15, six animals from each group were sacrificed, weighted and the cheek pouch mucosa was clinically analyzed. Statistical analysis was made considering the time x treatment interaction through the SPSS Statistics 18.0® software. The multiple comparison was made by the Generalized Estimation Equation test and adjusted by the Bonferroni test. Results: The animals from the Control group had significant lose of weight at the 10th day of the experiment. The laser treatment at preventive, therapeutic and combined form presented mucosits scratching reduction in comparison to the control group. However there was no statistic difference between the mucositis scores at the groups that received treatment. Conclusion: The low level laser, independent of the used protocol, is efficient to clinical reducing oral-inducted mucositis by 5-FU in hamsters.